Expression of Human Epidermal Growth Factor Receptor-2 Status and Programmed Cell Death Protein-1 Ligand Is Associated With Prognosis in Gastric Cancer - Lv, Huifang; Zhang, Junling; Sun, Keran; Nie, Caiyun; Chen, Beibei; Wang, Jianzheng; Xu, Weifeng; Wang, Saiqi; Liu, Yingjun; Chen, Xiaobing (Frontiers in Oncology, 2021)
Background PD-L1 and HER-2 as routine biomarkers in gastric cancer (GC). However, little research has been done to investigate the correlation among PD-L1, HER-2, immune microenvironment and clinical features in GC. Methods Between Jan. 2013 and May 2020, a total of 120 GC patients treated with chemotherapy were admitted to Henan Tumor Hospital. We retrospectively identified PD-L1, HER-2 level before chemotherapy and abstracted clinicopathologic features and treatment outcomes. Univariate and multivariate survival analyses were performed to assess the relationship between PD-L1/HER-2 levels and progression-free survival (PFS). The mRNA and tumor microenvironment of 343 patients with GC from The Cancer Genome Atlas (TCGA) was used to explore the underlying mechanism. Results We retrospectively analyzed 120 patients with gastric cancer, including 17 patients with HER-2 positive and 103 patients with HER-2 negative GC. The results showed that the expression of PD-L1 was closely correlated with HER-2 gene status, with statistical significance (P =0.015). Patients with PD-L1/HER-2 positive obtained lower PFS compared to PD-L1/HER-2 negative (mPFS: 6.4 vs. 11.1 months, P=0.014, mPFS: 5.3 vs. 11.1 months, P=0.002). And the PD-L1 negative and HER-2 negative had the best PFS than other groups (P=0.0008). In a multivariate model, PD-L1 statue, HER-2 statue, tumor location and tumor differentiation remained independent prognostic indicators for PFS (P<0.05). The results of database further analysis showed that the proportion of PD-L1+/CD8A+ in HER-2 negative patients was higher than that in HER-2 positive patients (37.6% vs 20.3%). While PD-L1-/CD8A- was significantly higher in HER-2 positive patients than HER-2 negative patients (57.8% vs. 28.8%). In addition, it showed that not only CD4+T cells, macrophages and CD8+T cells, but also the associated inflammatory pathways such as IFN-γ/STAT1were were associated with HER-2. Conclusion HER-2 status could predict the efficacy of immune checkpoint inhibitors, and HER-2 status combined with PD-L1 level could predict the prognosis of GC patients.